Applicability of water quality index in assessing the portability of Kaani River in Ogoni axis of Rivers State, Nigeria - Anate, Sumaila Ganiyu; Edori, Onisogen Simeon (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Superficial water samples were composed from four locations namely, Maa di Binnise Igbara water side (station 1), mann stream (station 2), woman stream (station 3) and Nwii ke maa kor stream (station 4), along the Ogoni axis of Kaani River and were evaluated for water quality index. Based on several water quality parameters, a water quality index gives a single figure that represents the total water quality at a specific place and time. One of the best ways to inform the public, policymakers, and those involved in water quality management about trends in water quality is through the indices. In contrast to the typical approach of employing physicochemical parameters to evaluate the water quality state of a water body, the weighted arithmetic index method of Ashwani and Anish (2009) was employed in this work for the calculation of the water quality index of the River. The ten most important parameters known to contribute greatly to water quality were considered in the analysis. The observed mean values from the analysis of the physicochemical parameters were; pH 6.56±0.11, EC 158.13±48.25 μS/cm, turbidity 6.08±4.39 NTU, DO 5.29±0.79 mg/l, BOD 5.88±0.78 mg/l, TDS 72.0±20.75 mg/l, TDS 30.88±2.44 mg/l, TA 61.55±4.36 mg/l, TH 49.38±6.73 mg/l and nitrate 0.75±0.35 mg/l respectively. All the tested physicochemical parameters through the locations except turbidity, dissolved oxygen and biochemical oxygen demand fall within the tolerable boundary of WHO (2007). The water quality index value of the Kaani River was 74.038 which indicated that the River has been compromised and is not an excellent source of water suitable for human consumption.